2008
DOI: 10.1128/aem.01784-07
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model for Inactivation of Feline Calicivirus, a Norovirus Surrogate, by Heat and High Hydrostatic Pressure

Abstract: Noroviruses, which are members of the Caliciviridae family, represent the leading cause of nonbacterial gastroenteritis in developed countries; such norovirus infections result in high economic costs for health protection. Person-to-person contact, contaminated water, and foods, especially raw shellfish, vegetables, and fruits, can transmit noroviruses. We inactivated feline calicivirus, a surrogate for the nonculturable norovirus, in cell culture medium and mineral water by heat and high hydrostatic pressure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 46 publications
4
68
2
Order By: Relevance
“…HPP affects only noncovalent bonds, such as ionic, hydrophobic, and hydrogen bonds (9,25,30), which suggests that primary and secondary protein structures remain intact. However, HPP may alter quaternary and tertiary structures and/or conformation of a protein that results in a misfolding or unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…HPP affects only noncovalent bonds, such as ionic, hydrophobic, and hydrogen bonds (9,25,30), which suggests that primary and secondary protein structures remain intact. However, HPP may alter quaternary and tertiary structures and/or conformation of a protein that results in a misfolding or unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…Using these surrogates, it has been demonstrated that a number of nonthermal processing technologies, such as gamma irradiation, electron beam irradiation, and ultrasound, are not effective at inactivating viruses (1,13). In contrast, both MNV and FCV can be effectively inactivated by highpressure processing (HPP), suggesting that HPP may be a feasible technology to eliminate human NoV in high-risk foods (5,10,25,27). However, whether these surrogates truly represent human NoV inactivation by HPP remains unknown.…”
mentioning
confidence: 99%
“…Also similar thermal inactivation rates at 63°C and 72°C were noted for FCV and MNV-1 (Cannon et al, 2006). Dispersed reductions of FCV for the same time-temperature combination were achieved by (Doultree et al, 1999) and (Buckow et al, 2008). The experimental setup was likely to be responsible for the differences in heat inactivation rates.…”
Section: Effects Of Treatments Used In Food Processing On Virusesmentioning
confidence: 94%